Diversity of interaction solutions to the (2+1)-dimensional Ito equation - Ma, Wen-Xiu; Yong, Xuelin; Zhang, Hai-Qiang (Computers & mathematics with applications (1987), 2018)
We aim to show the diversity of interaction solutions to the (2+1)-dimensional Ito equation, based on its Hirota bilinear form. The proof is given through Maple symbolic computations. An interesting characteristic in the resulting interaction solutions is the involvement of an arbitrary function. Special cases lead to lump solutions, lump-soliton solutions and lump-kink solutions. Two illustrative examples of the resulting solutions are displayed by three-dimensional plots and contour plots.